2008
DOI: 10.1158/1078-0432.ccr-08-0816
|View full text |Cite
|
Sign up to set email alerts
|

The Desmoplastic Reaction Surrounding Hepatic Colorectal Adenocarcinoma Metastases Aids Tumor Growth and Survival via αv Integrin Ligation

Abstract: Purpose: The treatment of metastatic colorectal carcinoma represents a major clinical challenge.We investigated the hypothesis that the desmoplastic reaction within the liver elicited by metastatic adenocarcinoma, characterized by collagen I deposition and altered collagen IV distribution, promotes the growth and survival of hepatic colorectal carcinoma metastases. Experimental Design: Partialhepatectomy specimens for metastatic colorectaladenocarcinoma were examined immunohistochemically for differential inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 41 publications
3
42
0
2
Order By: Relevance
“…[16][17][18][19][20] However, for some cell lines from colorectal hepatic metastases, in vitro interactions with type-I collagen have been reported to promote growth, survival, and chemoresistance via a v integrin ligation. 21 Vermeulen et al 1 described the growth patterns as three fundamentally different types of expansion, yet the mixed-type pattern and the variable growth patterns among multiple and recurrent metastases, documented by Eefsen et al 4 and the present study, suggest interrelations between the growth patterns. Based on a study on autopsied livers, which showed that the replacement pattern was highly predominant among micrometastases o1 mm, Terayama et al 22 hypothesized that the replacement pattern is simply a stage that precedes the pushing and desmoplastic patterns.…”
Section: Figurementioning
confidence: 37%
“…[16][17][18][19][20] However, for some cell lines from colorectal hepatic metastases, in vitro interactions with type-I collagen have been reported to promote growth, survival, and chemoresistance via a v integrin ligation. 21 Vermeulen et al 1 described the growth patterns as three fundamentally different types of expansion, yet the mixed-type pattern and the variable growth patterns among multiple and recurrent metastases, documented by Eefsen et al 4 and the present study, suggest interrelations between the growth patterns. Based on a study on autopsied livers, which showed that the replacement pattern was highly predominant among micrometastases o1 mm, Terayama et al 22 hypothesized that the replacement pattern is simply a stage that precedes the pushing and desmoplastic patterns.…”
Section: Figurementioning
confidence: 37%
“…Several previous studies have suggested that integrins expression and colon cancer invasion are correlated. In one study, Conti and colleagues reported that integrin av inhibition in CRC specimens from hepatic metastases caused a significant reduction in tumor cell proliferation on collagen plates (34). A previous study utilizing animal models showed that the resection of CRC dramatically increased malignant cell adhesion within the liver, and blocking of a2 integrin prevented the increase of colorectal hepatic metastases (35).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the present study, we clearly demonstrated that the presence of DR was significantly correlated with SM depth in nonpedunculated SICRCs. Although it is still unclear whether DR represents a form of host defense against tumor invasion or metastasis [25,26], the initiation of DR may be associated with destruction of the muscularis mucosae [17]. In support of this idea, DR is hardly ever observed in intramucosal carcinoma [14], but is known to be involved in the biological changes in the muscularis mucosae during tumor invasion [27,28].…”
Section: Discussionmentioning
confidence: 99%